Tourism transformations in protected area gateway communities - Slocum, Susan L.; Wiltshier, Peter; Read, John B. IV (CABI, 2022)
"Gateway communities are those located adjacent to protected areas and are often the communities most impacted by tourism visitation and are dependent on tourism revenue. This book presents informed, interpreted, and nuanced approaches towards protect area management and conservation, based on bottom-up local experiences by the gateway communities"--